Aromatic polycarbonates bearing pendant maleimide groups via functional monomer approach: synthesis and characterization - Nagane, Samadhan S.; Kuhire, Sachin S.; Ichake, Amol B.; Rajamohanan, P. R.; Wadgaonkar, Prakash P. (Journal of Polymer Research, 2019)
A new bisphenol containing pendant maleimide group, viz., 4, 4'-(5-maleimidopentane-2, 2-diyl) diphenol (BPA-MA), was synthesized starting from commercially available 4, 4'-bis (4-hydroxyphenyl) pentanoic acid. Aromatic (co)polycarbonates possessing pendant maleimide groups were synthesized by solution polycondensation of BPA-MA or varying mixtures of BPA-MA and bisphenol-A (BPA) with triphosgene in dry dichloromethane in the presence of triethylamine as a base. Inherent viscosities and number average molecular weights of (co)polycarbonates were in the range 0.46-0.66 dL/g and 24,600-36,700, respectively, indicating the formation of reasonably high molecular weight polymers. Tough, transparent, and flexible films could be cast from chloroform solutions of these (co)polycarbonates. (Co)polycarbonates were characterized using FT-IR, H-1 NMR, C-13 NMR spectroscopy, XRD, TGA and DSC analysis. The chemical modification of a representative copolycarbonate containing pendant maleimide groups was carried out quantitatively using thiol-maleimide Michael addition reaction with two thiol compounds, namely, 4-chlorothiophenol and 1-adamantanethiol. Additionally, it was demonstrated that copolycarbonate containing pendant maleimide groups could be used to form insoluble cross-linked gel by reaction with a multifunctional thiol cross-linker, namely, pentaerythritol tetrakis(3-mercaptopropionate).
Keywords: Aromatic polycarbonate; Cross-linking; maleimide group; Thiol-maleimide reaction; Triphosgene

Design and synthesis of aromatic polyesters bearing pendant clickable maleimide groups - Nagane, Samadhan S.; Kuhire, Sachin S.; Jadhav, Uday A.; Dhanmane, Sushilkumar A.; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2019)
A bisphenol bearing pendant maleimide group, namely, N-maleimidoethyl-3, 3-bis(4-hydroxyphenyl)-1-isobenzopyrrolidone (PPH-MA) was synthesized starting from phenolphthalein. Aromatic (co)polyesters bearing pendant maleimide groups were synthesized from PPH-MA and aromatic diacid chlorides, namely, isophthaloyl chloride (IPC), terephthaloyl chloride (TPC), and 50:50 mol % mixture of IPC and TPC by low temperature solution polycondensation technique. Copolyesters were also synthesized by polycondensation of different molar proportions of PPH-MA and bisphenol A with IPC. Inherent viscosities and number-average molecular weights of aromatic (co)polyesters were in the range of 0.52-0.97 dL/g and 20,200-32,800 g/mol, respectively indicating formation of medium to reasonably high-molecular-weight polymers. C-13 NMR spectral analysis of copolyesters revealed the formation of random copolymers. The 10% weight loss temperature of (co)polyesters was found in the range 470-484 degrees C, indicating their good thermal stability. A selected aromatic polyester bearing pendant maleimide groups was chemically modified via thiol-maleimide Michael addition reaction with two representative thiol compounds, namely, 4-chlorothiophenol and 1-adamantanethiol to yield post-modified polymers in a quantitative manner. Additionally, it was demonstrated that polyester containing pendant maleimide groups could be used to form insoluble crosslinked gel in the presence of a multifunctional thiol crosslinker. (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019, 57, 630-640
Keywords: crosslinking; maleimide group; modification; polyesters; thiol-maleimide